Facile folding of insulin variants bearing a prosthetic C-peptide prepared by α-ketoacid-hydroxylamine (KAHA) ligation - Boross, Gábor N. (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
The chemical synthesis of insulin is an enduring challenge due to the hydrophobic peptide chains and construction of the correct intermolecular disulfide pattern. We report a new approach to the chemical synthesis of insulin using a short, traceless, prosthetic C-peptide that facilitates the formation of the correct disulfide pattern during folding and its removal by basic treatment. The linear precursor is assembled by an ester forming α-ketoacid-hydroxylamine (KAHA) ligation that provides access to the linear insulin precursors in good yield from two readily prepared segments. This convergent and flexible route provides access to various human, mouse, and guinea pig insulins containing a single homoserine mutation that shows no detrimental effect on the biological activities.